ETHICAL ASPECTS OF CLINICAL INVESTIGATIONS IN CHILDREN - S.V. Topolyanskaya (Педиатрическая фармакология, 2010)
Clinical investigations in children must meet all the requirements, making to such kinds of investigations in adults. To the present time a number of international instructions and documents, regulating the holding of clinical investigations of medications in children is developed. The basic ethical problems, arising up during preparation and holding of clinical investigations are described in the article in details: informed consent for participating in investigation, estimation of the degree of the risk for the child-participant, decreasing of this risk, and also minimization of fear and pain, which arising up in the process of investigation. Following of the ethical principles gives not only the opportunity of improvement of pharmacotherapy in children, but also allows to observe the inseparable rights of the most vulnerable category of patients. Key words: clinical investigations, ethical principles, consent, risk, children. (Pediatric Pharmacology. – 2010; 7(3):6-11)